Electro–Chemo–Mechanical Issues at the Interfaces in Solid‐State Lithium Metal Batteries - Wang, Peng; Qu, Wenjie; Song, Wei‐Li; Chen, Haosen; Chen, Renjie; Fang, Daining (Advanced functional materials, 2019)
Effective solid‐state interfacial contact of both the cathode and lithium metal anode with the solid electrolyte (SE) are required to improve the performance of solid‐state lithium metal batteries (SSBs). Electro–chemo–mechanical coupling (ECMC) strongly affects the interfacial stability of SSBs. On one hand, mechanical stress strongly influences interfacial contact and causes side reactions. On the other hand, electrochemical reactions such as lithium deposition cause mechanical deformation and stress at electrode/SE interfaces. To solve the degradation/failure problems of interfaces and provide guidelines to construct high‐performance SSBs, the ECMC at electrode/SE interfaces should be comprehensively investigated. In this review, the problems associated with ECMC at electrode/SE interfaces are summarized. The interfacial degradation/failure mechanisms, including the contact and electrochemical stability of interfaces, are introduced. Mechanical factors affecting interfacial contact and lithium deposition are highlighted. Experimental observation and computational analysis methods for electrode/SE interfaces are then summarized. Strategies to construct stable electrode/SE interfaces, such as assembling stress and wetting layers to improve interfacial contact, 3D SE structure, and plating stress relief to suppress lithium dendrite formation, are reviewed. The remaining challenges to better understanding ECMC and related solutions to aid SSB development are discussed. The failure mechanisms of electrode/solid electrolyte (SE) interfaces in solid‐state lithium metal batteries (SSBs) involve multiscale and multiphysical field coupling. Various in situ observation technologies and corresponding theoretical approaches have been used to investigate the degradation mechanism of SSBs. Based on the experimental and theoretical results, well‐established solutions are explored to construct stable electrode/SE interfaces in SSBs.